2018
DOI: 10.1016/j.vaccine.2018.05.110
|View full text |Cite|
|
Sign up to set email alerts
|

Immunogenicity and safety of the adjuvanted recombinant zoster vaccine co-administered with the 23-valent pneumococcal polysaccharide vaccine in adults ≥50 years of age: A randomized trial

Abstract: No immunologic interference was observed between RZV and PPSV23 when co-administered in adults ≥50 years. No safety concerns were raised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Recombinant and adjuvanted vaccines, such as RZV, can be administered concomitantly, at different anatomic sites, with other adult vaccines, including COVID-19 vaccines (17). Concomitant administration of RZV with other adult vaccines ¶ ¶ ¶ ¶ has been studied, and there was no evidence for interference in the immune response to either vaccine or of safety concerns (18)(19)(20). Coadministration of RZV with adjuvanted influenza vaccine (Fluad) and COVID-19 vaccines is being studied.…”
Section: Clinical Guidance § § § §mentioning
confidence: 99%
“…Recombinant and adjuvanted vaccines, such as RZV, can be administered concomitantly, at different anatomic sites, with other adult vaccines, including COVID-19 vaccines (17). Concomitant administration of RZV with other adult vaccines ¶ ¶ ¶ ¶ has been studied, and there was no evidence for interference in the immune response to either vaccine or of safety concerns (18)(19)(20). Coadministration of RZV with adjuvanted influenza vaccine (Fluad) and COVID-19 vaccines is being studied.…”
Section: Clinical Guidance § § § §mentioning
confidence: 99%
“…Simultaneous administration of the HZ/su inactivated vaccine with the 23va lent pneumococcal polysaccharide vac cine (PPSV23) was studied in 865 adult participants age 50 years and older (aver age age 63.2 years) in an open randomized trial [23]. Here as well, participants were assigned to the coadministration or con trol arm at a ratio of 1:1, and the vaccina tion scheme in both arms corresponded to that of the study on the simultaneous administration of QIV.…”
Section: Coadministration With Other Vaccinesmentioning
confidence: 99%
“…Two large Phase III studies demonstrated efficacy in older adults [28,29]. Additional studies are ongoing/completed to investigate the long-term duration of the immunogenicity and the efficacy of RZV, as well as safety and immunogenicity of vaccine coadministrations and of RZV when given at least 5 years after previous ZVL vaccination [75][76][77].…”
Section: Rzv Clinical Development Program In Adults 50+ Yoamentioning
confidence: 99%
“…Additional Phase III studies in adults 50+ YOA have evaluated RZV coadministered with quadrivalent influenza vaccine or with 23-valent pneumococcal polysaccharide vaccine [76,87]. Results indicate that coadministration with both vaccines was well tolerated and immunogenic, and no immunologic interference between the administered antigens has been observed [76,87]. A study to assess coadministration with reduced antigen content combined diphtheria-tetanus and acellular pertussis vaccine was recently completed (NCT02052596).…”
Section: Coadministrationmentioning
confidence: 99%